Effects of the charge characteristics of polycarboxylate superplasticizers on the adsorption and the retardation in cement pastes. (January 2015) - Zhang, Yan-Rong; Kong, Xiang-Ming; Lu, Zhen-Bao; Lu, Zi-Chen; Hou, Shan-Shan
Abstract: The traditional polycarboxylate (PC) superplasticizers are usually negatively charged polymers, in which the carboxylate functionalities are responsible for their adsorption on cement surface driven by electrostatic interaction. This paper investigates the impacts of the charge characteristics of PC co-polymers on their adsorption behaviors and the retardation effects on cement hydration. PC co-polymers with variation of their charge species were synthesized by co-polymerizing the macro-monomer with selected anionic and cationic monomers. Adsorption and impacts on cement hydration of the monomers, their homo-polymers and the PC co-polymers were studied in cement pastes by total organic carbon tests and calorimetry respectively. Results show that in cement pastes, no adsorption and retardation were observed for the monomers while for their corresponding homo-polymers, different extents of adsorption and retardation were found. Charge characteristics of PC co-polymers strongly determine their adsorption behaviors and retardation effects, in the order of COO − > SO3 − > N + .